2020
DOI: 10.19102/icrm.2020.110602
|View full text |Cite
|
Sign up to set email alerts
|

Same-day Discharge after Subcutaneous Implantable Cardioverter-defibrillator Implantation is Safe and Cost-effective

Abstract: The feasibility and safety of same-day discharge after transvenous implantable cardioverter-defibrillator implantation is well-established. However, subcutaneous ICDs (S-ICDs) are now increasingly being implanted, and the feasibility, safety, and potential cost savings associated with same-day discharge after S-ICD placement has not been widely investigated. In a small cohort of patients (n = 24) who underwent S-ICD implantation at our institution, 54% were successfully discharged on the same day as their impl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…There is growing data supporting the safety, feasibility, and cost-effectiveness of this approach after CIED implants (transvenous pacemaker/ICD/CRT, sub-cutaneous ICDs, and Micra® leadless pacemaker). 2 , 4 , 13 Similarly, patients undergoing electrophysiological studies and ablation for SVT or right-sided atrial flutter/tachycardia have been safely discharged home on the same day for years. 14 More recently there is mounting evidence on the safety and cost-effectiveness of SDD in patients undergoing ablation for atrial fibrillation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is growing data supporting the safety, feasibility, and cost-effectiveness of this approach after CIED implants (transvenous pacemaker/ICD/CRT, sub-cutaneous ICDs, and Micra® leadless pacemaker). 2 , 4 , 13 Similarly, patients undergoing electrophysiological studies and ablation for SVT or right-sided atrial flutter/tachycardia have been safely discharged home on the same day for years. 14 More recently there is mounting evidence on the safety and cost-effectiveness of SDD in patients undergoing ablation for atrial fibrillation.…”
Section: Discussionmentioning
confidence: 99%
“… 1 Over the past decade, there has been a shift to same-day discharge (SDD) for a variety of electrophysiology procedures. 2–4 The COVID-19 pandemic has increased the need to limit the time patients spend in the hospital. The American College of Cardiology (ACC) has issued an expert decision pathway for SDD after percutaneous coronary intervention (PCI).…”
Section: Introductionmentioning
confidence: 99%
“…Outcomes regarding readmission were available in four studies. 18,20,22,23 Pooled readmission rates were 17.6%, and 17.5% in SDD and HO groups respectively. There were no statistically significant differences in readmission between SDD and HO groups (pooled OR = 0.95, 95%CI: 0.74-1.21, p = .667, I 2 = 49.3%).…”
Section: Readmissionmentioning
confidence: 96%
“…A total of eight studies from 2012 to June 2020 were included in this meta-analysis. [16][17][18][19][20][21][22][23] There were 1 RCT, three prospective cohort studies, and four retrospective cohort studies. The final analysis included a total of 61,602 patients (4,153 in SDD group and 57,449 in HO group) with a follow-up time range from 0.5 to 16 months.…”
Section: Description Of Included Studiesmentioning
confidence: 99%
“…Management, the results of a small series of patients at Riverside Hospital in Columbus, Ohio are reported. Among patients (n = 24) who underwent S-ICD, half of whom were sent home on the same day as device implantation (n = 13), Swinning et al, 3 found no specific increased risk. A reasonable health care system cost savings of $1,664.48 per patient was reaped with the protocol of same-day early discharge after S-ICD implantation.…”
Section: In This Issue Of the Journal Of Innovations In Cardiac Rhythmmentioning
confidence: 98%